Perlodinella mazehaoi sp. nov., a new species of Perlodidae (Plecoptera) from Inner Mongolia of China - Chen, Zhi-Teng (Zootaxa, 2019)
A new species of the perlodid genus Perlodinella Klapálek, 1912, P. mazehaoi sp. nov. from Inner Mongolia of northeastern China is described and illustrated based on the male, the female and eggs. The aedeagus and egg described herein are the first known for the genus Perlodinella. Morphological comparisons between the new species and congeners are given. This species is the first record of Perlodinella from Inner Mongolia.